2012
DOI: 10.1002/jsfa.5620
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid, tocopherol and carotenoid content in herbage and milk affected by sward composition and season of grazing

Abstract: All four herbages tested were suitable for production of milk with a high content of beneficial compounds. Thus any of these herbages could be used in production of such differentiated milk based on a large proportion of grazing in the ration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…Information about tocopherol content in fresh forage is not consistent (Kalac 2012). Larsen et al (2012) reported that the concentrations of α-tocopherol in various grasses and legumes vary considerably with plant maturity and, to a lesser extent, with species. They reported a concentration of 36 mg in 1 kg DM lucerne mix.…”
Section: Discussionmentioning
confidence: 99%
“…Information about tocopherol content in fresh forage is not consistent (Kalac 2012). Larsen et al (2012) reported that the concentrations of α-tocopherol in various grasses and legumes vary considerably with plant maturity and, to a lesser extent, with species. They reported a concentration of 36 mg in 1 kg DM lucerne mix.…”
Section: Discussionmentioning
confidence: 99%
“…As the 2 pastures did not differ in the total proportions of non-legume dicotyledons (hypothesis 1), but mainly in the proportions of red clover and white clover it was not likely that differences in botanical composition would affect milk FA composition as Larsen et al (2012) and Wiking et al (2010) found only minor effects of grazing red clover or white clover on milk FA composition. If this is true, we suggest that annual and biannual non-legume docotyledons commonly found in herbage from SP have similar effects on milk FA composition as perennial dicotyledons usually found in herbage from LP.…”
Section: Effect Of Pasture Type On Milk Compositionmentioning
confidence: 92%
“…Compared to grass (Poaceae) based silages, silages based on mixed leys with grass and red clover (Trifolium pratense L.) or white clover (Trifoilum repens L.) increase the milk-fat proportions of C18:3 n-3 (Dewhurst et al, 2003). No or inverse effects on proportions of C18:3 n-3 are reported when cows graze red clover rich pastures compared to white clover rich pastures (Larsen et al, 2012;Wiking et al, 2010). Soder et al (2006) found increasing milk-fat proportions of C18:2c9t11 for cows grazing more botanical diverse forage mixtures, however, C18:3 n-3 was not affected.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, interest on tocopherol and carotenoid composition of botanical species of natural grasslands has emerged due to their potential use as biomarkers of foods derived from grass feeding animals such as milk, cheese and meat (Prache, Cornu, Berdagué, & Priolo, 2005;Prache, Priolo, & Grolier, 2003). However, studies on tocopherol and carotenoid composition of plants from natural grasslands are scarce in the scientific literature (Cardinault et al, 2008;Larsen et al, 2012;Noziére et al, 2006). The most frequently referenced methods for the analysis of carotenoids and tocopherols in plant material are primarily based on solid-liquid extraction followed by separation by high-performance liquid chromatography (HPLC) ( Table 1, and references therein).…”
Section: Introductionmentioning
confidence: 99%